Konsumsi Jus Kurma terhadap Peningkatan Kadar Trombosit pada Pasien Demam Berdarah Dengue di Wilayah Kota Jambi - Apni Riama Simorangkir; Asmeriyani Asmeriyani (Jurnal Akademika Baiturrahim Jambi, 2022)
Dengue Fever (DHF) is an infectious disease caused by a virus. One of the signs of DHF is a decrease in the number of platelets (thrombocytopenia). The recommended management of thrombocytopenia is an increase in adequate nutrition and adequate electrolyte fluids. One way that is recommended is to consume dates  juice. The content of date palm juice that can directly increase the platelet count is a number of polysaccharides such as rhamnose, arabinose, xylose, mannose, galactose and glucose because it is an ingredient in the formation of platelet granules in megakaryocytes in the bone marrow.The purpose of this study was to determine how much influence the administration of date palm juice had on increasing platelet levels in patients with Dengue Hemorrhagic Fever. The sample in this study amounted to 30 people, 15 people in the treatment group and 15 people in the control group. The hypothesis test that will be used in the bivariate analysis uses a T-test. The results of the study concluded that there was a significant difference between the results of the 3rd day of the treatment group and the control group. The t-value of the treatment group is greater, namely 16,089 than the t-value of the control group, which is 10,373, this indicates that the treatment group experienced an increase in platelet levels higher than the platelet level in the control group.